Electrocatalysis of cathodic hydrogen and anodic oxygen evolution in alkaline water electrolysis by in situ activation procedures - Schmidt, T.; Wendt, H. (Electrochimica acta, 1994)
The possibility of in situ activation of oxygen evolving anodes and hydrogen evolving cathodes in alkaline water electrolysers has been investigated. It is possible to activate anodes by depositing on them cobalt oxide or iron oxide or an even more active mixture of both. In all three cases the oxygen evolution overpotential at 1 A cm −2 which amounts under standard conditions to approximately 350 mV improves by approximately 80–100 mV. However, activation by iron oxide is not stable as the solubility of Fe 2O 3 in the electrolyte is too high, the coating dissolves and iron is precipitated on the cathode. Also cobalt oxide coatings are subject to slow deterioration—though to a much slower rate than the deterioration of iron oxide coatings. Most interesting is the fact that combined deposition of iron and cobalt oxide leads to a much more stable catalyst, which shows undiminished activity over at least 4000 h. Furthermore it is shown, that it is possible to precipitate in situ metallic ruthenium on hydrogen evolving cathodes in alkaline water electrolysers. The cathodic overpotential is thus reduced to less than −100 mV at 1 A cm −2 and 120°C. The use of complexing agents yields in rather smooth and compact ruthenium deposits with enhanced long-term stability. Copper substrates may be used instead of nickel resulting in relatively low costs.